Basic criteria and classification scheme for bacteriophages acting against cholera vibrios of the classical and El Tor biotypes - Bystryi, N F; Drozhevkina, M S (Journal of hygiene, epidemiology, microbiology, and immunology, 1979)
In accordance with the principles, nomenclature and taxonomic tests recommended by the TCNV for the systematization of viruses, cholera and El Tor phages were classified in all categories of the taxonomic hierarchy. On the basis of this classification, all known cholera bacteriophages could be affiliated to the biological type Vira, sub-type Deoxyvira, class 2/D B -- Deoxybinala, family Phagoviridae, genus Phagovirus vibrio and species Phagovirus cholerae. Phagovirus cholerae includes homologous series III-D, IV-D and V-D with 10 serologic types representing the smallest taxonomic units. At same time, phages of the remaining families with a single-strainded structure of DNA and RNA have so far not been detected for cholera vibrios.
Keywords: sérotypizace; Bacteriophage Typing; elektronová mikroskopie; antigeny bakteriální; fagotypizace; Antigens, Bacterial; Bacteriophages; Vibrio cholerae; Serotyping; Microscopy, Electron; bakteriofágy